Model for generating the climate impact of prefabricated power systems - Balaji, Ashwin; Lianminthang Naulak, Joseph (My University, 2023)
Abstract With the ever-rising emissions, reaching the temperature below 2 degrees climate change goal is becoming more far-fetched. The current focus is on accurately calculating, modelling and finding ways to reduce carbon emissions which is escalating yet necessary for achieving sustainable solutions. This study will focus on the climate impact within the power transmission system, providing a comprehensive model for its evaluation for an electrical substation. This study integrates Life cycle Assessment, its methodologies and the stages involved in an LCA study. Furthermore, performing an analysis of the components including the materials and working of the substation, evaluation and quantification through sensitivity analysis. A life cycle assessment (LCA) is conducted from cradle-to-grave to quantify the emissions. Real-world data are collected from various suppliers and available databases, literature reviews are conducted to enhance the model’s accuracy and validation to assess the climate impact. The results and findings highlight in detail the contributing factors behind carbon emissions. Further stressing the type of energy source, materials, production, and power losses affect the outcome for the environment. The model provides comprehensive insight and acts as a tool for stakeholders and producers a step towards reducing their carbon footprint for these systems and adopting more sustainable energy practices.
Keywords: Keywords: Life Cycle Assessment, Substations, Climate Impact, Carbon Footprint, cradle-to-grave